Design of a foundational sciences curriculum: Applying the ICAP framework to pharmacology education in integrated medical curricula - Kelly M. Quesnelle; Naunihal T. Zaveri; Stephen D. Schneid; Joe B. Blumer; John L. Szarek; Marieke Kruidering; Michael W. Lee (Wiley, 2021)
Abstract Expectations for physicians are rapidly changing, as is the environment in which they will practice. In response, preclerkship medical education curricula are adapting to meet these demands, often by reducing the time for foundational sciences. This descriptive study compares preclerkship pharmacology education curricular practices from seven allopathic medical schools across the United States. We compare factors and practices that affect how pharmacology is integrated into the undergraduate medical education curriculum, including teaching techniques, resources, time allocated to pharmacology teaching, and assessment strategies. We use data from seven medical schools in the United States, along with results from a literature survey, to inform the strengths and weaknesses of various approaches and to raise important questions that can guide future research regarding integration of foundational sciences in medical school and health professions' curricula. In this comparative study, we found that there is significant heterogeneity in the number of hours dedicated to pharmacology in the preclerkship curriculum, whereas there was concordance in the use of active learning pedagogies for content delivery. Applying the ICAP (Interactive, Constructive, Active, Passive) Framework for cognitive engagement, our data showed that pharmacology was presented using more highly engaging pedagogies during sessions that are integrated with other foundational sciences. These findings can serve as a model that can be applied beyond pharmacology to other foundational sciences such as genetics, pathology, microbiology, biochemistry, etc.